Peace at all costs: Hungarian Foreign Policy Discourse and the Russo-Ukrainian War Abstract - Dudlák, Tamás (POLARITIES, 2023)
The war in Ukraine has challenged the fundamentally pro-Russian and anti-Ukrainian Hungarian government policy. Before the war, the Hungarian government utilized the discourse of the uncorrupted East and the declining West. In this paper, I assume that the Hungarian government effectively incorporated its discourse of the Russian-Ukrainian war into its earlier anti-Western framework. Similarly, there is a continuity in the principles of Hungarian foreign policy previously applied and pronounced by Orbán (protection of sovereignty and national interest, pragmatism, mutual respect, and the cost-benefit principle).